A comparative study of the physical activity guidelines for children and adolescents from five countries and WHO - Hu, Donglin; Zhou, Shi; Crowley-McHattan, Zachary J.; Liu, Zhiyun (Frontiers in Public Health, 2024)
This study presented a narrative review of the six latest sets of guidelines on physical activity for children and adolescents from Australia, Canada, China, the United Kingdom, the United States and WHO, and analysed the history of the development of the guidelines; the policy context in which the guidelines were developed; and the main subjects of the guidelines.The core elements of the latest guidelines were identified and compared, including frequency, intensity, duration (time), and type of physical activity, assessment intensity of physical activity, and risk prevention for physical activity participation. There is an urgent need for obtaining the latest scientific evidence to support and update the contents of the Chinese guidelines. We therefore make the following recommendations for future revisions of the Chinese guidelines based on the findings of this study: (1) to update the recommended frequency, intensity, duration, and type of physical activities that meet the needs for Chinese children and adolescents; (2) to update the methods for assessing physical activity intensity, and identifying and managing the risk factors in participating in physical activity; and (3) to incorporate analyses and reviews of school physical education curriculum for effectively achieving the adequate levels of physical activity.